Detection of 16S rRNA and 23S rRNA gene mutations in multidrug resistant Salmonella serovars isolated from different sources using RNA sequencing method - Thanh Viet, Nguyen; Bich Thuy, Vo Thi (Vietnam Journal of Biotechnology, 2020)
The rapid emergence of resistant bacteria is occurring worldwide. Antibiotic resistance is a serious problem for human beings because pathogenic microorganisms that acquire such resistance void antibiotic treatments. Bacterial antibiotic resistance mechanisms include efflux, reduced influx, modification and degradation of the drug, as well as mutation, modification or overexpression of the target. However, our knowledge as to how bacteria acquire antibiotic resistance is still fragmented, especially for ribosome-targeting drugs. Salmonella is a leading cause of foodborne salmonellosis in the world. The number of antibiotic resistant isolates identified in humans is steadily increasing, suggesting that the spread of antibiotic resistant strains is a major threat to public health. Salmonella is commonly identified in a wide range of animal hosts, food sources, and environments, but our knowledge as to how Salmonella resistance to antibiotics is still fragmented in this ecologically complex serovar. Therefore, the aim of this study was to support for finding novel mechanisms that render bacteria resistant to the ribosome targeting antibiotics, we screen for antibiotic resistant 16S and 23S ribosomal RNAs (rRNAs) in multidrug resistant Salmonella serovars isolated from raw retail meats isolated from Hanoi, Vietnam. Bioinformatic analysis identified 193 unknown novel mutations (64 mutations in 16S rRNA and 129 mutations in 23S rRNA genes). These mutations might play a role in streptomycin resistant in Salmonella serovars. These results suggest that uncharacterized antibiotic resistance mutations still exist, even for traditional antibiotics. This study is only a preliminary kind, further validation before they are applied in Salmonella or other closely related species are required